Scrotal myasis with multiple inoculation: case report - Carrillo-Ñañez, Leonidas (2024)
Myasis is an ectoparasitic infection caused by human (as well as some domestic and wild animals) tissue and cavity infestation by _Diptera_ larvae, generally flies. This condition is more frequent in tropical areas, and it may also occur in places with deficient sanitary conditions. We present the case of a patient from a tropical area, a farmer who reported exposure to dead animals, wild animals, and flies, in whom forunculoid type cutaneous myasis in the scrotum region was diagnosed, which also had superimposed infection. This patient received therapy with intravenously administered antibacterial agents, a single dose of oral ivermectin. Locally, orifices were occluded with basil. This was followed by the forceps-aided extraction of 20 larvae in two sessions. The patient had good progression. We consider this case is an original contribution, given that genitalia infection by fly larvae is unfrequently reported, even in endemic areas. Two cases of genital myasis have been reported in the national literature: one in a young woman, and the other in an elderly woman. Nonetheless, as far as we know, scrotal myasis has never been reported in Peru.